A Cross Sectional Study Of The Prevalence Of Depression Among The Male Post-Graduate Medical Students Of Gauhati Medical College And Hospital, India - Heemanshu Shekhar Gogoi (European Scientific Journal, ESJ, 2016)
Background: Depression is defined according to the WHO as a common mental disorder, characterized by sadness, loss of interest or pleasure, feelings of guilt or low self-worth, disturbed sleep or appetite, feelings of tiredness, and poor concentration. One-fourth to one-third of the post-graduate medical trainees and residents develop clinical depression at some point in their training period although much higher rates were reported in some other studies. Objective: To evaluate the prevalence of depression along with its different degrees among the male post-graduate students in Gauhati Medical College and Hospital. Material and method: This study was performed on 120 male post-graduate medical students according to inclusion and exclusion criterias. The ‘Hamilton Depression Rating Scale (HAM-D)’ was used for evaluating depression. Result: The prevalence of depression among the male post-graduate medical students is 37% (mild depression-16%, moderate depression-14%, severe depression-7% and lastly very severe depression -0%) in Gauhati Medical College and Hospital. Conclusion: This study shows that the male post-graduate medical students are suffering from psychological distress which is leading them into depression. This issue should be properly addressed because of its possible impact on quality of health care services in teaching hospitals and on training outcome.